(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Oil shale utilisation losses reach 70% in some cases. These are closely related to legislation, backfilling and waste rock usage. Much smaller sections include production of oil, electricity and chemicals in which most of the research and development is performed today. Current urgent topics for investigating, testing and developing of oil shale mining related questions are backfilling, mechanical extracting of shale, fine separation, selective separation and optimised drilling and blasting. Reducing oil shale losses will be more actual in the future, because the depth of mining increases and the taxes for resource and pollutants are increasing as well.